PELATIHAN PEMANFAATAN BARANG BEKAS MENJADI BARANG BERGUNA DI YAYASAN HUDATUL FALLAH, CISEENG, BOGOR - Rizka Wahyuni Amelia; Widya Intan Sari; Arif Hidayat (Abdi Jurnal Publikasi, 2023)
The purpose of holding this Community Service activity is for Training on the Utilization of Used Goods into Useful Goods at the Hudatul Fallah Foundation in accordance with actual and current developments. Apart from that, it can move Board members to be able to educate the environment and become a program in the millennial era as it is today. By using group discussions, this counseling educates the management of the Hudatul Fallah Foundation on the utilization of various used waste into useful items. The results of the activity are increasing motivation for entrepreneurship by resource persons, demonstration activities for making business products made from used waste as well as counseling activities regarding how these products are made as entrepreneurial activities.